Identifying the Technological Drivers of e-Learning and Analyzing Them in Iran’s Higher Education (Emphasizing Engineering Education) - Gholam Ali Montazer; Tayyebeh Gashool Darehsibi; Mohammad Hassan Abbasi (آموزش مهندسی ایران, 2022)
Nowadays, e-learning has become an essential aspect of education and learning. Being informed of the key factors of e-learning advancement is of high importance to determine the vision, strategies, and policies in top-level organizations, companies, educational institutions, and enterprises involved in education. In this paper, we discuss technological drivers of e-learning and extract the most important factors according to technology hype cycle. The research has been performed through archival and documentary research and using information attained from published scientific references, reports, documents, and press releases. Main goals of this paper are (1) identifying technological drivers of e-learning and (2) analyzing status of Iran’s higher education according to the identified drivers. The result of the study shows that technological drivers of e-learning are: personalized and adaptive learning, mobile learning, social learning platforms, blended learning, gamification, simulation, cloud computing, integration and interoperability, xAPI standard, virtual reality, massive open online courses (MOOC), and video content management. Moreover, investigation shows that these technologies have not been used extensively in Iran. The current status of e-learning in Iran shows that the activities done in this area are not so coherent, systematic, and unified with the technology transitions. What is necessary to rectify this situation is to change the point of view to the e-learning and exploit the technology in a systematic way in policies, plans, and implementation. Being at the start of the new century and simultaneously formulating Seventh National Development Plan creates an opportunity for universities and Ministry of Science, Research, and Technology to include national policies and programs in that plan. Consequently, they can provide the possibility of rectifying the current path in electronic education in Iran and exploiting its advantages for education system, in a period of 5 years duration.